NEW COMBINATIONS IN PHELIPANCHE (OROBANCHACEAE) - Foley, M. J. Y. (Edinburgh Journal of Botany, 2007)
AbstractAs a result of recent genetic work, four taxa previously described by the author within Orobanche are now transferred to Phelipanche Pomel (Orobanchaceae); in addition, one of them, originally described as a subspecies, is raised to specific rank.